2003
DOI: 10.1101/gad.258203
|View full text |Cite
|
Sign up to set email alerts
|

The POU proteins Brn-2 and Oct-6 share important functions in Schwann cell development

Abstract: The genetic hierarchy that controls myelination of peripheral nerves by Schwann cells includes the POU domain Oct-6/Scip/Tst-1 and the zinc-finger Krox-20/Egr2 transcription factors. These pivotal transcription factors act to control the onset of myelination during development and tissue regeneration in adults following damage. In this report we demonstrate the involvement of a third transcription factor, the POU domain factor Brn-2. We show that Schwann cells express Brn-2 in a developmental profile similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
297
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(314 citation statements)
references
References 42 publications
13
297
0
2
Order By: Relevance
“…Transcription of the Dhh gene has not been studied, and the regulatory region that mediates its expression in Schwann cells has not yet been identified. However, work by Jaegle et al (2003) had shown that 19 kb of genomic sequence around the Dhh gene are sufficient to achieve expression of a Cre transgene in Schwann cells. This region encompasses all three Dhh exons as well as upstream and downstream sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription of the Dhh gene has not been studied, and the regulatory region that mediates its expression in Schwann cells has not yet been identified. However, work by Jaegle et al (2003) had shown that 19 kb of genomic sequence around the Dhh gene are sufficient to achieve expression of a Cre transgene in Schwann cells. This region encompasses all three Dhh exons as well as upstream and downstream sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The abil- ity of Brn-1 and Brn-2 to compensate for the loss of Pou3f1 was demonstrated using mutant knock-in mice in which Brn-1 (or Brn-2) was inserted into the Pou3f1 locus effectively replacing Pou3f1 expression. The Brn-1 knock-in mice displayed normal Egr2 expression and onset of myelination, whereas Brn-2 knock-in mice manifested a partial rescue of the aberrant myelination phenotype present in Pou3f1-deficient mice (Jaegle et al, 2003;Friedrich et al, 2005). These findings indicate that Brn-1 and Brn-2 are functionally capable of rescuing the myelination delay of the Pou3f1 null mice and provide additional evidence that, as previously hypothesized, Pou3f1 is required for the initiation of myelination (Jaegle and Meijer, 1998;Zorick et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, myelination is accompanied by the production of huge amounts of myelin proteins and lipids. The entry into the myelination program in Schwann cells is controlled on the transcriptional level by factors like Egr2 (Krox-20), Pou3f1 (Oct-6/Scip/Tst-1) and Pou3f2 (Brn2) that interact with Sox10 to drive expression of myelin genes (Topilko et al, 1994;Bermingham et al, 1996;Jaegle et al, 2003;Finzsch et al, 2010; see also Svaren and Meijer, 2008, and the references herein). In addition, lipid biosynthesis genes are coordinately regulated, and the Srebp/Scap transcription factors and the control of their expression play important roles in lipid production (Verheijen et al, 2009;Norrmen et al, 2014).…”
Section: Entry Into the Myelination Programmentioning
confidence: 99%